The effects of nutrient timing on training adaptations inresistance-trained females - Pihoker, A. A.; Peterjohn, A. M.; Trexler, E. T.; Hirsch, K. R.; Blue, M. N. M.; Anderson, K. C.; Ryan, E. D.; Smith-Ryan, A. E. (Journal of Science and Medicine in Sport, 2019)
Objectives: The purpose of this study was to determine the effects of pre- vs. post-workout nutrition on strength, body composition, and metabolism in trained females over 6 weeks of high intensity resistance training (HIRT). Design: Forty-three trained females (mean ± SD; age: 20.5 ± 2.2 yrs; height: 165.2 ± 5.7 cm; body mass: 66.5 ± 11.4 kg) were measured for strength, body composition, and metabolic variables before and after a HIRT intervention. Participants were randomized using a 2:2:1 matched block randomization scheme by baseline leg press strength into a group that consumed a 1:1.5 carbohydrate-protein supplement (16 g CHO/25 g PRO) pre-training (PRE), post-training (POST), or no supplement (CON). Methods: Dual-energy X-ray absorptiometry was used to evaluate fat mass (FM), lean mass (LM), and percent fat (%fat). Strength was analyzed using a one repetition max on the leg and bench press (LP1RM and BP1RM, respectively). Participants completed HIRT twice per week for 6 weeks. At the first and last trainings, metabolic variables [resting energy expenditure (REE) and respiratory exchange ratio, RER] were measured. Results: There were no significant differences between groups for any changes in body composition variables or LP1RM (p = 0.170-0.959). There were significant differences for BP1RM (p = 0.007), with PRE and POST experiencing greater increases than CON (p = 0.010 and 0.015, respectively). REE changes were not significant between groups (p = 0.058-0.643). PRE demonstrated greater fat oxidation (RER) at 30 min post-exercise (p = 0.008-0.035). Conclusion: Peri-workout nutrition is potentially important for upper body strength and metabolism. PRE may be more effective for promoting fat utilization immediately post-workout.